Hidden in Plain Sight: Clinical Informaticians are the Oncology Subspecialists You Did Not Know You Needed. Issue 2 (February 2022) - Kim, E.; Bitterman, D.S.; Kann, B.H.; Mak, R.H.; Moreno, A.C.; Upadhyay, V.A.; Warner, J.L.; Zhang, H.M.
Abstract: Clinical informatics is a young, diverse and rapidly growing field. We asked eight clinical informaticians from a variety of oncology specialties, training pathways and careers for personal narratives to illustrate the wide spectrum of clinical informatics careers. Primary clinical specialties included radiation oncology, medical/haematology oncology and palliative care. Training pathways included fellowship, non-fellowship formal training and informal training. Careers included clinical care, research, operations and industry. We summarised common themes and advice for trainees. We hope to raise awareness of clinical informatics among trainees and oncologists to reveal new career opportunities and to avoid inadvertently taking clinical informatics and informaticians for granted.